Moral epistemology - Zimmerman, Aaron (Routledge, 2010)
How do we know right from wrong? Do we even have moral knowledge? Moral epistemology studies these and related questions about our understanding of virtue and vice. It is one of philosophy's perennial problems, reaching back to Plato, Aristotle, Aquinas, Locke, Hume and Kant, and has recently been the subject of intense debate as a result of findings in developmental and social psychology.